Half-light [compact disc] - Rostam, 1983- (Nonesuch, 2017)
Half-Light is the debut album from Rostam, who is known for his work with Vampire Weekend and produced each of their three albums. The kaleidoscopic album features fifteen songs written, produced, and performed by Rostam in his Los Angeles home studio.